CASE REPORTSThoracic aorta aneurysm successfully operated on during pregnancy - Mokrzycki, Krzysztof; Biskupski, Andrzej; Kuligowska, Ewelina; Listewnik, Mariusz; Brykczyński, Mirosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
We present the case of an asymptomatic 26-year-old female patient with a huge thoracic aneurysm discovered at a routine echo screening. The patient had previously been operated on for coarctation of the aorta in childhood and also had diagnosed bicuspid aortic valve. The operation was carried out in extracorporeal circulation at the 22nd week of gestation without any complications. A few months later in the 38th week of pregnancy a baby girl was delivered by cesarean section with an Apgar score of 10. The patient is scheduled for implantation of a stent graft to the descending aorta, because the CT of the chest done a few months after delivery confirmed presence of a significant aneurysm located just below the left subclavian artery.